Ascorbic acid and melatonin reduce heat-induced performance inhibition and oxidative stress in Japanese quails - Şahin, Nurhan; Onderci, M; Şahin, Kazım; Gursu, MF; Smith, MO (Taylor & Francis Ltd, 2004)
1. The effects of ascorbic acid ( l -ascorbic acid) and melatonin supplementation on performance, carcase characteristics, malondialdehyde (MDA) as lipid peroxidation indicator, ascorbic acid, retinol, tocopherol and mineral status in the Japanese quail ( Coturnix coturnix japonica ) exposed to high ambient temperature were evaluated. 2. Two hundred and forty Japanese quails (10 d old) were randomly assigned to 8 treatment groups consisting of 10 replicates of three birds each. The birds were kept in a temperature-controlled room at 22degreesC (Thermoneutral, TN groups) or 34degreesC (for 8 h/d; 09:00 to 17:00 h; Heat stress, HS groups). Birds in both TN and HS were fed either a basal (control) diet or the basal diet supplemented with 250 mg of l -ascorbic acid/kg of diet (Ascorbic acid group), 40 mg of melatonin/kg of diet (Melatonin group) or both (Ascorbic acid + Melatonin group). 3. Supplementing heat-stressed quails with ascorbic acid and melatonin improved performance compared with the control group. Effects generally were greatest in quails supplemented with both ascorbic acid and melatonin. 4. Although supplementation did not consistently restore the concentrations of serum ascorbic acid, retinol and tocopherol to those of TN groups, these concentrations increased significantly with supplementation. Furthermore, serum and liver MDA and serum cholesterol and glucose concentrations were lower in the supplemented groups than in the heat-stressed controls. 5. Within each environment, excretion of Ca, P, Mg, Zn, Fe and Cr were lowest in the combination group and, in all cases, highest in the HS group. Interactions between diet and temperature were detected for live weight gain, cold carcase weight, MDA, ascorbic acid, tocopherol concentrations and excretion of zinc. 6. The results of the study indicate that ascorbic acid and melatonin supplementation attenuate the decline in performance and antioxidant and mineral status caused by heat stress and such supplementation may offer protection against heat-stress-related depression in performance of Japanese quails.
Keywords: Vitamin-C; Broiler-Chickens; Growth-Hormone; Mineral Concentrations; Ambient-Temperature; Lipid-Peroxidation; Protein-Turnover; Skeletal-Muscle; Supplementation; Serum